Методи моделювання та програмні засоби для забезпечення надійності та живучості ОЕС України з використанням нових мікропроцесорних пристроїв керування режимами електроенергетичних систем - Авраменко, В.М.; Крилов, В.О.; Черненко, П.О.; Прихно, В.Л.; Мартинюк, О.В.; Юнєєва, Н.Т. (Технічна електродинаміка, 2011)
The object of an article is to present basic results of a scientific work according to plans of NAS of Ukraine. They are: methodics of the use of voltage phasors (WAM-systems) for the electric power systems (EPS) state estimation and for estimation of steady state stability level in the EPS sections; methodics and software for the automated calculations by the personal computers of short circuit currents in the nodes of complex electric network of 􀈿PS and for determination of settings of EPS protection units in the microprocessor devices of REL521 the company 􀈺􀈼􀈼, which are used for 750…110 kV overhead lines; for medium-term forecasting of electro-consumption and electro-loading of UPS of Ukraine; for operative removal of the broken limits of electric parameters in power system elements.